Modifying effect of a common polymorphism in the interleukin-6 promoter on the relationship between long-term exposure to traffic-related particulate matter and heart rate variability. - Martin Adam (Public Library of Science (PLoS), 2014)
Background Exposure to particulate matter (PM) has been associated with an increase in many inflammatory markers, including interleukin 6 (IL6). Air pollution exposure has also been suggested to induce an imbalance in the autonomic nervous system (ANS), such as a decrease in heart rate variability (HRV). In this study we aimed to investigate the modifying effect of polymorphisms in a major proinflammatory marker gene, interleukin 6 (IL6), on the relationship between long-term exposure to traffic-related PM10 (TPM10) and HRV. Methods For this cross-sectional study we analysed 1552 participants of the SAPALDIA cohort aged 50 years and older. Included were persons with valid genotype data, who underwent ambulatory 24-hr electrocardiogram monitoring, and reported on medical history and lifestyle. Main effects of annual average TPM10 and IL6 gene variants (rs1800795; rs2069827; rs2069840; rs10242595) on HRV indices and their interaction with average annual exposure to TPM10 were tested, applying a multivariable mixed linear model. Results No overall association of TPM10 on HRV was found. Carriers of two proinflammatory G-alleles of the functional IL6 -174 G/C (rs1800795) polymorphism exhibited lower HRV. An inverse association between a 1 µg/m3 increment in yearly averaged TPM10 and HRV was restricted to GG genotypes at this locus with a standard deviation of normal-to-normal intervals (SDNN) (GG-carriers: -1.8%; 95% confidence interval -3.5 to 0.01; pinteraction(additive) = 0.028); and low frequency power (LF) (GG-carriers: -5.7%; 95%CI: -10.4 to -0.8; pinteraction(dominant) = 0.049). Conclusions Our results are consistent with the hypothesis that traffic-related air pollution decreases heart rate variability through inflammatory mechanisms.